PERAN STRATEGIS PENDIDIKAN KEWARGANEGARAAN PADA DEKONSTRUKSI NORMA PATRIARKI DAN PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA - Ichsan, Muhammad; Siti Tiara Maulia; Melisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Domestic violence (KDRT) in Indonesia is manifestation of gender injustice structures normalized by patriarchal norms. This study aims to analyze the strategic role of Citizenship Education (PKn) in deconstructing patriarchal norms and preventing domestic violence through a qualitative approach with a literature review method. The result of the study show that KDRT is not merely an indivudal problem, but a result of unequal power relations legitimized culturally and structurally. Meanwhile, conventional PKn with a state-centric paradigm is considered to fail in critiquing these inequalities and even further reinforces gender bias. Therefore, a recontruction of PKn towards a human-centric paradifm is needed, focusing on human rights, substantive gender equality, and social justice. Its impelemntation requires operational strategies at the micro, meso and macro levels. Even when facing challenges such as cultural bias and weak inter-agency coordination, opportunities for success remain open through transformative education approaches, the utilization of community social capital, and the convergence of constitutional value with positive law within a holistic and sustainable framework.